BFS Human Behaviour Model for Traffic Safety - Molan, Marija; Molan, Gregor (Promet - Traffic&Transportation, 2011)
The Butterfly Flower Shower (BFS) Human Behaviour Model describes human behaviour in each demanding, possible accidental situation. The BFS human behaviour model is presented for a traffic situation. The key elements (perception, cognition, reaction) of the human behaviour are identified. Also possible limitations and errors in all elements of human behaviour are presented. The model is presented as the butterfly on the flower under the shower of interventions. The flower is environment describing traffic infrastructure composed of the environment, technology and organization. The body of the butterfly is human cognition with personality and motivation. The left wing of the butterfly is the driver’s perception. The right wing of the butterfly is the driver’s reaction. The butterfly presents the driver, the flower presents the road – the traffic infrastructure and the shower presents the shower of humanization interventions into the traffic infrastructure and into the driver. The drops from the shower are related to identified limitations in the traffic infrastructure and to the driver. They are focused on the improvements of perception, cognition and reaction abilities of the driver also with investments into the traffic infrastructure.